Socialization of Digital Transactions and E-Commerce to Improve Students' Understanding of Sharia Principles at Karawang Islamic Middle School - Titi Komala; Adinda Aprilia Saraswati; Aang Suryana; Oyoh Bariah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
With the development of communication and information technology, society's transaction patterns have changed dramatically, especially in terms of sharia economics. Electronic commerce, or e-commerce, has become the main alternative for consumers and business people to carry out transactions quickly. Since Indonesia is a Muslim-majority country, it is very important that e-commerce practices comply with sharia principles, such as honesty, transparency, and freedom from gharar (uncertainty) and maysir (gambling). Sharia-compliant digital transactions are very much needed, especially among students. The aim of this activity is to increase Karawang Islamic Middle School students' understanding of sharia economic concepts and the characteristics of halal digital transactions. By using educational methods, it is hoped that students can understand the types of transactions that are in accordance with sharia and develop a critical view when choosing a digital platform for transactions. Students not only gain theoretical knowledge through these socialization activities, but they are also motivated to participate actively in discussions about their experiences of online transactions. As a result, they have the ability to prepare themselves to face challenges in the digital world while adhering to sharia principles. By understanding in depth, students are expected to help create a stronger sharia economic ecosystem in the internet era.